Analysis of maxillary teeth and soft tissue profiles among Tibetan and Han Chinese females with facial symmetry for orthodontic treatment planning - Deng, Lijia; Lei, Jinmei; Li, Minjie; Song, Hongjie; He, Hong (Frontiers in Surgery, 2024)
The evaluation of maxillary teeth and soft tissue profiles is a critical component of orthodontic diagnosis and treatment planning. This study aimed to evaluate the correlation between the sagittal position of maxillary anterior teeth and facial profile esthetics among Tibetan and Han Chinese adult females for optimizing orthodontic diagnosis and treatment planning. A total of 100 Tibetan Chinese and 100 Han Chinese adult females with good facial symmetry were recruited. The smiling facial profile images with the maxillary central incisors and forehead in full view were taken based totally on the same standard. The photo measurement and head position were adjusted using the pictureenhancing software. The reference traces associated with forehead inclinations were utilized to assess the anteroposterior (AP) positions of the maxillary central incisors. The results showed that a round forehead was the dominant forehead shape for Tibetan (93%) and Han (55%) Chinese females. In Tibetan females, 85% of the maxillary central incisors were found to be located between the forehead's anterior limit line (the Fall line) and the goal anterior limit line (the Gall line), with 15% located posterior to the Fall line. This distribution manifested a strong association with incisor position and forehead inclination (R 2 = 0.742). In Han females, 83% of the maxillary central incisors were located between the Fall line and the Gall line, with 12% posterior to the Fall line and 5% anterior to the Gall line. The positions of the maxillary central incisors exhibited a strong relationship with forehead inclination (R 2 = 0..827). The maxillary central incisors were close to the aesthetic line in both ethnic groups, while forehead inclinations were correlated with AP maxillary incisor position. These findings demonstrated that there was a close relationship between the incisor position of Tibetan and Han females with facial symmetry and the forehead FFA factor, indicating a reference in oral hard and soft tissues for optimizing orthodontic diagnosis and treatment planning in terms of facial contour.